Uneven demographic consequences of the 2022 disease outbreak for the sea urchin Diadema antillarum in Puerto Rico - Ruber Rodríguez-Barreras; Claudia Patricia Ruiz-Diaz; Marcos A. Quiñones-Otero; Carlos Toledo-Hernández (PeerJ, 2023)
Pervasive epizootic events have had a significant impact on marine invertebrates throughout the Caribbean, leading to severe population declines and consequential ecological implications. One such event was the regional collapse of herbivory, partly caused by the Diadema antillarum mortality event in 1983–84, resulting in a trophic cascade and altering the structure of reef communities. Consequently, there was a notable decrease in coral recruitment and an increase in the coverage of macroalgae. Nearly four decades later, in early 2022, the Caribbean basin experienced another widespread mass mortality event, further reducing the populations of D. antillarum. To assess the effects of this recent mortality event on the current demographics of D. antillarum, we surveyed eight populations along the eastern, northeastern, northern, and northwestern coast of Puerto Rico from May to July 2022, estimating their population density, size distribution, and disease prevalence. Additionally, the study compared these population parameters with data from four sites previously surveyed in 2012 and 2017 to understand the impact of the recent mortality event. The survey conducted in 2022 showed varying population densities at the surveyed reefs. Some populations exhibited mean densities of nearly one individual per square meter, while others had extremely low or no living individuals per square meter. The four populations with the highest density showed no evidence of disease, whereas the four populations with the lowest D. antillarum densities exhibited moderate to high disease prevalence. However, when considering all sites, the estimated disease prevalence remained below 5%. Nevertheless, the comparison with data from 2012 and 2017 indicated that the recent mortality event had a negative impact on D. antillarum demographics at multiple sites, as the densities in 2022 were reduced by 60.19% compared to those from the previous years. However, it is still too early to determine the severity of this new mortality event compared to the 1983–84 mortality event. Therefore, it is imperative to continue monitoring these populations.